Heat pump and thermal energy storage: Influences of photovoltaic, the control strategy, and price assumptions on the optimal design - Wüllhorst, Fabian; Reuter-Schniete, Jonas; Maier, Laura; Müller, Dirk (Renewable energy, 2024)
Combining heat pump, thermal energy storage, and photovoltaic is a common option to increase renewable energy usage in building energy systems. While research finds that optimal system design depends on the control, design guidelines neglect an influence of (1) photovoltaic, (2) the supervisory control, and (3) prices assumptions on the design of heat pump and thermal energy storage. We analyze how these influences may impact the optimal design. To analyze possible impacts, a pre-screening approach is used to identify relevant model input combinations with a potentially high influence on the optimal design. Applying a simulation-based design optimization with a detailed building energy system model, we optimize three cases: no photovoltaic, no supervisory control, and a state-of-the-art supervisory control. Results indicate that cost optimal design does not change with photovoltaic or the supervisory control, but heat pump size increases with higher electricity prices. For the storage, maximizing the size achieves high self-sufficiency degrees, but cost optimal design changes only for selected price assumptions. Overall, we find that neglecting photovoltaic and surplus control in the system design is a valid assumption. However, price assumptions should be included to allow simple but optimal design rules in current guidelines. [Display omitted] •Simulation-based design and control optimization using detailed, nonlinear Modelica models.•Pre-screening of model inputs relevant to the research question.•Analysis of different objectives including total costs, operational costs, efficiencies and component behavior.•Photovoltaic and the control strategy show little influence on the optimal design.•Price assumptions influence the optimal heat pump, but not the thermal energy storage size.